Tingkat Kerusakan dan Strategi Pengelolaan Mangrove di Kawasan Taman Nasional Togean Provinsi Sulawesi Tengah. - Afriani, Early; Naharudin, Naharudin; Toknok, Bau (Mitra Sains, 2023)
This study aims to: (1) determine the potential and condition of the mangrove forest ecosystem in Muara Bandeng Village, Una-una District, Tojo Una-Una Regency. (2) determine the level of damage to mangroves in Muara Bandeng Village, Una-una District, Tojo Una-Una Regency. (3) formulate recommendations for alternative strategies for the further development and management of mangrove forests in Muara Bandeng Village, Una-una District, Tojo Una-Una Regency. The sampling method is the checkered line method. This research is a quantitative descriptive research . The results of the study show the following: (1) The potential of mangrove forests in Muara Bandeng Village, Una – Una Sub-district, Tojo Una – Una Regency can still be developed to help the community's economy with support and direction from the local government and other environmentalist organizations. The condition of the mangrove ecosystem in Muara Bandeng Village is in a damaged condition. (2) Based on the analysis, it shows that the level of damage to the mangrove forest in Muara Bandeng Village is in the damaged category. This is supported by the results of the analysis of the level of damage to mangroves. Based on the analysis of the level of ecosystem degradation, the TNS value is 225. (3) strategic recommendations Strategies that can be carried out are as follows : (a) Organizing skills training in managing mangroves (ecotourism and nursery) to increase people’s income, (b) Increase information shared through new technology to attract foreign tourists.